Incidence of epithelial lesions of the conjunctiva in a review of 12,102 specimens in Canada (Quebec) - Alves,Luiz Filipe de Albuquerque (2011)
PURPOSE: The purpose of this study was to assess the relative frequency of epithelial lesions of the conjunctiva in Canada. METHODS: A retrospective study of 12,102 consecutive cases received during 16 years (1993-2009) at the Henry C. Witelson Ocular Pathology Laboratory in Montreal, Canada, was performed. Demographic data was retrieved from histopathological request forms and specimens were categorized and analyzed by mean percentage. The relative frequency of epithelial lesions of the conjunctiva from a single center in Canada, representing the province of Quebec was reviewed. RESULTS: Of the 12,102 specimens reviewed, 273 were conjunctival lesions (2.25%), including 86 epithelial tumors (0.71%) of the conjunctiva that comprised the studied sample. The average age of these patients was 59.9 ± 17.6 years, and gender distribution was 66 (69%) males and 30 (31%) females. Fifteen lesions (17.4%) were classified as squamous cell papillomas (mean age, 57.3 ± 16.7 years). Within the ocular surface squamous neoplasia (OSSN) spectrum, there were 10 (11.6%) actinic keratosis (63.8 ± 17.6 years), 27 (31.3%) cases of conjunctival intraepithelial neoplasia (CIN) with variable degrees of atypia (mild to moderate) (63.9 ± 15.3 years), 15 (17.4%) carcinomas in situ (66.7 ± 18.0 years), and 17 (19.7%) squamous cell carcinomas (SCC) (56.2 ± 19.4 years). Two other rare cases of malignant tumors included one basal cell carcinoma and one mucoepidermoid carcinoma. CONCLUSIONS: The distribution of our sample is similar to the one reported by the American Forces Institute of Pathology (AFIP) in 1994. When we compare our sample to others coming from countries with high levels of sunlight exposure, we found a lower incidence of ocular surface squamous neoplasia, including squamous cell carcinomas in Canada.